The influence and association of blood on transfer catheter and vaginal microbiota on pregnancy outcomes in frozen-embryo transfer cycles - Fu, Li; Zhou, Yingshun; Xu, Ling; Hu, Yue O.O.; Chen, Shaowei; Wang, Mingyong; Jiang, Xia; Zheng, Meiling; Wu, Qiang; Fu, Junjiang (JOURNAL OF REPRODUCTIVE IMMUNOLOGY, 2025)
The effect of blood and mucus on the catheter on pregnancy outcomes in frozen-embryo transfer (FET) cycles remains relatively under-investigated. To evaluate the influence of the presence of blood and mucus on the transfer catheter, along with the characteristics of vaginal microbiota on pregnancy outcomes in FET cycles, we comprehensively analyzed the clinical data of 816 patients. We meticulously recorded the potential traces of blood and mucus on the catheter following embryo transfer (ET). We examined three key outcome parameters including implantation rate (IR), clinical pregnancy rate (CPR), and biochemical pregnancy rate (BPR). Our results demonstrated that the presence of blood on the catheter was associated with a marked decrease in BPR and CPR, whereas the presence of mucus had no significant impact on BPR, CPR, and IR. To further elucidate whether the influence of blood on the catheter on pregnancy outcomes was mediated by vaginal microbiota imbalance, we examined the vaginal microbiota using 16S rRNA gene sequencing and conducted in-depth statistical analyses and correlation studies. Interestingly, the alpha and beta diversity of the vaginal microbiota between the blood group and non-blood group differed significantly. Importantly, the abundance of Lactobacillus was markedly decreased in the blood group. Our results indicate that the negative effect of the blood on the catheter on pregnancy may be attributed to the imbalance of vaginal microbiota. These results provide new insights into the potential mechanisms underlying the association between vaginal microbiota and blood on the catheter and their impact on pregnancy outcomes in FET cycles. •The impact of vaginal microbiota, blood, and mucus on the transfer catheter on pregnancy outcomes inFET was evaluated.•The blood group showed a significantly decreased biochemical pregnancy rate (BPR) and clinical pregnancy rate (CPR).•The alpha and beta diversity of the vaginal microbiota between the blood group and non-blood group differed significantly.•An imbalance of vaginal microbiota may be related to the presence of blood on the catheter and affect pregnancy outcomes.